2022
DOI: 10.3390/cancers14041041
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Time on Treatment with First-Line Pembrolizumab Monotherapy for Advanced NSCLC with PD-L1 Expression ≥ 50%: 3-Year Follow-Up Data

Abstract: Our aim was to evaluate real-world time on treatment (rwToT), overall and by KRAS mutation status, with first-line pembrolizumab monotherapy for advanced non-small cell lung cancer (NSCLC) in real-world oncology practice in the US. rwToT is a readily available, intermediate-range endpoint that is moderately to highly correlated with overall survival in clinical trials and real-world data. Using deidentified electronic medical record data, we studied patients with ECOG performance status (PS) of 0–2 who initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
5
16
0
Order By: Relevance
“…The negative effect of ECOG PS = 2 was also found in an American study based on deidentified electronic medical record data. 12 After a median follow-up of 34 months, the median real-world time on first-line pembrolizumab monotherapy was 7.4 (6.3-8.1) months for the entire cohort but only 2.1 (1.4-2.8) months for the 237 patients with ECOG PS = 2. 12 The same effect was also observed in a multicenter Japanese study on 40 elderly patients (median age 78.5 y) and/or ECOG PS = 2 (40%); 9 the objective response rate was 40.5% and the disease-control rate was 62%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The negative effect of ECOG PS = 2 was also found in an American study based on deidentified electronic medical record data. 12 After a median follow-up of 34 months, the median real-world time on first-line pembrolizumab monotherapy was 7.4 (6.3-8.1) months for the entire cohort but only 2.1 (1.4-2.8) months for the 237 patients with ECOG PS = 2. 12 The same effect was also observed in a multicenter Japanese study on 40 elderly patients (median age 78.5 y) and/or ECOG PS = 2 (40%); 9 the objective response rate was 40.5% and the disease-control rate was 62%.…”
Section: Discussionmentioning
confidence: 93%
“…3,4 That observation was echoed in other reports. [5][6][7][8][9][10][11][12] The results of a prospective, observational study on 40 patients with ECOG PS = 2 or ≥ 75 years old, with ≥ 1% PD-L1 expression on their aNSCLC cells showed that median (95% CI) OS on first-line pembrolizumab lasted 11.6 (1.4-NR) months for patients with ECOG PS = 2 and 11.6 (7.4-18.1) months for the elderly. 9 However, long-term, real-world efficacy data for pembrolizumab in this indication are scarcer.…”
mentioning
confidence: 99%
“…[3] It is often used as a surrogate effectiveness endpoint, showing a high correlation to progressionfree survival and a moderate-to-high correlation to overall survival. [4,5] As rwTTD is an important metric for drug effectiveness, it is routinely reported during the postclinical trial phase. [2,4,[6][7][8] Calculation of rwTTD in patient population is often equivalent to constructing a Kaplan-Meier (KM) curve, with each point representing the proportion of patients that are still on treatment at a specific time point.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] It is often used as a surrogate effectiveness endpoint, showing a high correlation to progression‐free survival and a moderate‐to‐high correlation to overall survival. [ 4,5 ] As rwTTD is an important metric for drug effectiveness, it is routinely reported during the post‐clinical trial phase. [ 2,4,6–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Because time to treatment discontinuation can be readily obtained from electronic medical records, this effectiveness endpoint is convenient to evaluate the efficacy of a drug that is already approved for public use 3 . It is often used as a surrogate effectiveness endpoint, showing high correlation to progression-free survival and moderate-to-high correlation to overall survival 4,5 . As rwTTD is an important metric for drug effectiveness, it is routinely reported during the post-clinical trial phase 2,4,[6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%